Konsepsi mahar perkawinan dalam pandangan penghulu di Kabupaten Merauke - Poniran, Poniran; Rahman, Hendra Yulia; Al Abza, M. Thohar (Prodi Hukum Keluarga Islam Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2025)
Dowry is an obligatory gift from the husband to the wife that is given before, during, or after the marriage contract as an integral part of the contract. Penghulu as marriage registration officials have a strategic role in understanding and explaining the forms of dowry that develop in the community. This research aims to identify variations in the form of dowry in Merauke Regency from the perspective of the Penghulu, and analyze this phenomenon through Lawrence M. Friedman's legal system approach which includes aspects of legal substance, structure and culture. The method used is field research with conceptual, historical, normative, and phenomenological approaches. The results show that the form of dowry in Merauke varies greatly, ranging from gold jewelry, precious metals, cash, a set of prayer tools, to a combination of other forms of dowry. In Friedman's perspective, this variation reflects the emergence of a new conception of dowry that is influenced by social change and the dynamics of local legal culture. This finding confirms that dowry is not just a symbol of marriage, but also a living reflection of law that is adaptive to the social and cultural realities of a multicultural society.